Analisis Deskriptif Pelaksanaan Program Adiwiyata di SDN Brenggong - Latoifit Toharoh; Suyoto Suyoto; Muflikhul Khaq (Perkumpulan Kualitama Edukatika Indonesia, 2021)
This study aims to describe the implementation of the Adiwiyata program at SDN Brenggong which contains 4 components in the Adiwiyata program as well as supervision in the implementation of the Adiwiyata program at SDN Brenggong. This type of research used in this research is qualitative research that is presented descriptively. The research subjects in this study were the principal, the Adiwiyata team, classroom teachers, school guards and students at SDN Brenggong. The data technique used was observation, interview and documentation. Data analysis techniques in this study include data, data reduction, data collection, and data collection. Test the validity of the data using the Miles and Huberman model with the use of reference materials, namely interview data supported by recorded interviews, while data from observations and documentation are supported by documents in the form of writing, pictures and photos so that the data can be trusted. The findings show that: (1) the implementation of environmentally sound policies has been carried out by changing the vision and mission regarding support for environmental management and the availability of the Adiwiyata program budget, the application applied is the 2013 curriculum integrated with an environmentally sound curriculum that is inserted in every lesson on the theme and contains self-development activities, namely environmental education that is included in extracurricular activities, participatory-based environmental activities carried out intensively within the school environment or outside the school environment by involving other agencies and management of environmentally friendly supporting facilities carried out intensively by school residents; and (2) constraints in implementing the Adiwiyata program are the condition of students who have not met the environmental sustainability requirements, the costs to support the Adiwiyata program and the time and time of the school members, especially teachers and employees. because they have to work well and have full facilities at school during this Covid-19 pandemic.